A retrospective 'real-world' cohort study of azole therapeutic drug monitoring and evolution of antifungal resistance in cystic fibrosis. Issue 1 (16th March 2021) - Di Paolo, M; Hewitt, L; Nwankwo, E; Ni, M; Vidal-Diaz, A; Fisher, M C; Armstrong-James, D; Shah, A
Abstract: Background: Individuals with cystic fibrosis (CF) have an increased susceptibility to fungal infection/allergy, with triazoles often used as first-line therapy. Therapeutic drug monitoring (TDM) is essential due to significant pharmacokinetic variability and the recent emergence of triazole resistance worldwide. Objectives: In this retrospective study we analysed the 'real-world' TDM of azole therapy in a large CF cohort, risk factors for subtherapeutic dosing, and the emergence of azole resistance. Methods: All adults with CF on azole therapy in a large single UK centre were included. Clinical demographics, TDM and microbiology were analysed over a 2 year study period (2015–17) with multivariate logistic regression used to identify risk factors for subtherapeutic dosing. Results: 91 adults were treated with azole medication during the study period. A high prevalence of chronic subtherapeutic azole dosing was seen with voriconazole (60.8%) and itraconazole capsule (59.6%) use, representing significant risk factors for subtherapeutic levels. Rapid emergence of azole resistance was additionally seen over the follow-up period with a 21.4% probability of CF patients developing a resistant fungal isolate after 2 years. No significant relationship was found however between subtherapeutic azole dosing and azole resistance emergence. Conclusions: Our study demonstrates a high prevalence of subtherapeutic azole levels in CF adults with increased risk using itraconazole capsules and voriconazole therapy. We show rapid emergence of azole resistance highlighting the need for effective antifungal stewardship. Further large longitudinal studies are needed to understand the effects of antifungal resistance on outcome in CF and the implications of subtherapeutic dosing on resistance evolution.